2022
DOI: 10.1021/acs.jpclett.2c02280
|View full text |Cite
|
Sign up to set email alerts
|

Stacking Is Favored over Hydrogen Bonding in Azaphenanthrene Dimers

Abstract: N-Doped polycyclic aromatic hydrocarbons have recently emerged as potential organic electronic materials. The function of such materials is determined not only by the intrinsic electronic properties of individual molecules but also by their supramolecular interactions in the solid state. Therefore, a proper characterization of the interactions between the individual units is of interest to materials science since they ultimately govern properties such as excitons and charge transfer. Here, we report a joint ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Note that the [1 + 1′]-REMPI spectra of the dimers of 1 and 3 around the S 1 ← S 0 origin transition were also recorded using ns lasers. They are already presented in the SI of ref , and the assignments have been confirmed.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Note that the [1 + 1′]-REMPI spectra of the dimers of 1 and 3 around the S 1 ← S 0 origin transition were also recorded using ns lasers. They are already presented in the SI of ref , and the assignments have been confirmed.…”
Section: Resultsmentioning
confidence: 64%
“…The spectrum of the phenanthridine dimer is given in Figure . A short [1 + 1′]-REMPI spectra of the dimer of 3 was recorded using ns lasers and is given in the SI of ref , confirming the position of the major band. The transition densities indicate collective excitations for pi2 , so the oscillator strength of the S 1 ← S 0 (blue) of pi2 is small, and its contribution to the spectrum can be ignored.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…In our previous study of the pyridine dimer, (Pyd) 2 , we also showed that the π–π stacked structure has the lowest energy. It should also be noted that recent work on the azaphenanthrene dimer also showed that the π–π stacked structure is more stable than the H-bonded planar structure . In Table , we listed the energies of three lowest-energy isomers of (Pyra)­(Bz) calculated with the B3PW91 + D3/aug-cc-pVDZ, ωB97XD/aug-cc-pVDZ, and CCSD­(T)/aug-cc-pVTZ//ωB97XD/aug-cc-pVDZ methods.…”
Section: Resultsmentioning
confidence: 99%